2018
DOI: 10.3847/1538-4357/aab158
|View full text |Cite
|
Sign up to set email alerts
|

The Updated BaSTI Stellar Evolution Models and Isochrones. I. Solar-scaled Calculations

Abstract: The Updated BaSTI Stellar Evolution Models and Isochrones Hidalgo, S. L.; Pietrinferni, A.; Cassisi, S.; Salaris, M.; Mucciarelli, A.; Savino, A.; Aparicio, A.; Aguirre, V. Silva; Verma, K. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the numbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
251
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 293 publications
(267 citation statements)
references
References 154 publications
11
251
0
Order By: Relevance
“…We fit each entire CMD with five different stellar evolution libraries: Dartmouth (Dotter et al 2008), Padova (Girardi et al 2010), PARSEC (Bressan et al 2012), MIST (Choi et al 2016), and BaSTI (Hidalgo et al 2018). We find that for all CMDs analyzed in this paper the BaSTI 2018 models provide the best overall fits in terms of visual inspection of the residuals and through comparison of likelihood ratios between models.…”
Section: Methodsmentioning
confidence: 85%
“…We fit each entire CMD with five different stellar evolution libraries: Dartmouth (Dotter et al 2008), Padova (Girardi et al 2010), PARSEC (Bressan et al 2012), MIST (Choi et al 2016), and BaSTI (Hidalgo et al 2018). We find that for all CMDs analyzed in this paper the BaSTI 2018 models provide the best overall fits in terms of visual inspection of the residuals and through comparison of likelihood ratios between models.…”
Section: Methodsmentioning
confidence: 85%
“…Much of this discrepancy is driven by differences in the isochronal ages, which is likely attributable to differences between the MIST stellar evolution models and those used in the AMP analysis: a combination of the Aarhus stellar evolution code (ASTEC Christensen-Dalsgaard 2008a) and the adiabatic pulsation code (ADIPLS Christensen-Dalsgaard 2008b). We compared non-rotating, Solar-metallicity MIST isochrones for middle-aged stars with Solar-metallicity BaSTI isochrones (Pietrinferni et al 2004;Hidalgo et al 2018) and found that, for stars between 4 and 8 Gyrs, in the same effective temperature range as the asteroseismic stars, the age discrepancy between the two sets of models can be as large as 1-2 billion years. The MIST isochrones lie above the BaSTI isochrones on the HR diagram, leading to a systematic underprediction of ages.…”
Section: Test 3: Kepler Asteroseismic Starsmentioning
confidence: 99%
“…Although the BaSTI theoretical library has been recently updated (Hidalgo et al 2018), we chose to use the original models computed with the "canonical" set-up. This is because the new BaSTI release is still limited to the scaled-solar chemical abundance mixture, while α-enhanced tracks, more appropriate to model Tucana's old population, are currently being calculated (Hidalgo et al, in prep.).…”
Section: Interpreting the Hb Of Tucanamentioning
confidence: 99%